2022
DOI: 10.1186/s12889-022-12855-0
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices of parents towards antibiotic use in rural communities in Peru: a cross-sectional multicentre study

Abstract: Background The inappropriate use of antibiotics significantly contributes to the development of antibiotic resistance. There is limited information about the use of antibiotics among parents from rural areas in Peru. This study aimed to describe the knowledge, attitudes and practices towards antibiotics among parents of children < 5 years of age from rural communities in Peru; to explore the association between knowledge and attitudes towards antibiotics and to explore determinants of low kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 18 publications
8
18
1
Order By: Relevance
“…The degree of heterogeneity between groups for this subgroup was also statistically significant (P = 0.035). However, disregarding the one study from Latin America [58], subgroup analysis by region of the study reports found no difference between the Asian and African countries. Besides, the subgroup analysis by the children's age was also not significant.…”
Section: Outcome Measuresmentioning
confidence: 83%
See 2 more Smart Citations
“…The degree of heterogeneity between groups for this subgroup was also statistically significant (P = 0.035). However, disregarding the one study from Latin America [58], subgroup analysis by region of the study reports found no difference between the Asian and African countries. Besides, the subgroup analysis by the children's age was also not significant.…”
Section: Outcome Measuresmentioning
confidence: 83%
“…Antibiotic access sources for children in six of the remaining studies were mainly leftovers of home-stored drugs from previous prescriptions or uses [38,60,63,[66][67][68] and private clinics in the other two studies [44,59]. Eighteen of the included studies were conducted in uppermiddle-income countries [24,25,38,39,48,49,52,58,[60][61][62][63][64][65][66][67][68][69], while the remaining twelve [21-23, 40, 44-47, 50, 51, 54, 57] and nine [20, 41-43, 53, 55, 56, 59, 70] studies were conducted in lower-middle-income and low-income countries, respectively. The children in 14 studies used non-prescribed antibiotics for acute diarrhea [20, 21, 23, 24, 39, 40, 43, 49-52, 54, 57, 70]; the children in nine studies used them for acute upper respiratory tract infections [25,41,42,55,[59][60][61][62][63]; and the children in the remaining 16 studies used them for mixed-types of childhood illnesses [22, 38, 44-48, 53, 56, 58, 64-69].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of primary care physicians in peri-urban Lima, Peru, trimethoprim-sulfamethoxazole was found to be the most frequently preferred antibiotic to treat childhood dysentery [ 44 ]. Antibiotics are widely available in rural Peru and often given by parents to children without a prescription [ 45 ], which may be both a response to diarrheal disease and a contributing factor to AMR carriage. Kristiansson et al (2009) found that child or family members' recent antibiotic use was associated with a greater odds of resistance among multiple antibiotics in a study of urban communities in Amazonian Peru (Kristiansson et al, 2009) [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies have found that inappropriate antibiotic is associated with the following reseasons: antibiotic prescribing by non-infectious disease physicians [25], antibiotic dispensing in pharmacies [26,27], and public knowledge, attitude and practice of antibiotic use [28]. The factors determining the appropriate use of antibiotics by individuals are influenced by several aspects, including consumers' lack of knowledge about the appropriate use of antibiotics and their adverse effects [29][30][31], as well as their beliefs, expectations and personal experiences with antibiotics [32,33]. Knowledge, attitudes and practice (KAP) studies are often a preferred method to achieve this [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%